Desenvolvimento sustentável e empregos verdes no Brasil - Sugahara, Claudemir Ramos da Silva (2010)
This research discusses the relationship between development and environ-ment, aiming to define and quantify the Green Jobs in Brazil. In order to achieve this goal, concepts of development and sustainable development were approached and politics for implementation of strategies for environmentally sustainable growth were presented. It was also observed that, tied to the notion of "development", the notion of "sustainability" redefines the former one, even implying a change in the pre-analytic vision of the economy. In fact, the green economy needs the scale of the traditional economy resizing it as a subsystem of a larger system, namely the envi-ronment, which leads to the discussion of a sustainable economy. All these argu-ments are based on analysis of the results of Agenda 21, a document that would have officially started the discussion of economic sustainability as a practice of gov-ernment policies in Brazil. According to ILO (International Labor Organization), the term ''green jobs'' refers to occupations that both promote economic progress and contribute to the restoration of environmental quality. This term comprises occupa-tions that help protect the flora and fauna, and also reduce the consumption of ener-gy, natural resources and water, minimizing the impacts that nature has suffered over the centuries by the process of transformation of factors of production into goods and services . The classification of green jobs also requires decent work, which is sup-ported by worker‟s achievements in the social protection of labor and wages as well as in safe working conditions and labor rights. To introduce and to subsume Green Jobs in Brazil, the best data about jobs are provided by RAIS. Finally, we discussed ways to green jobs in the world and Brazil departing from the alternatives of energy supply and investments in alternative energy in the world and in Brazil, forestry activi-ties and going through buildings, transportation, basic industries, food and agricul-ture. The final remarks attempts to point out ways that would minimize the conflicts that distinguish and limit the classifications surrounding the green jobs, making them impenetrable islands in the Brazilian economic scenario